Say It Right the First Time - Loretta Malandro, Ph.D. (McGraw-Hill, 2003)
There are many different ways to produce high-performance results in organizations. Some companies create an internally competitive environment where the toughest, but not necessarily the most competent, rise to the top. Other organizations build a consensus culture where agreement replaces quality by reducing decisions to the lowest common denominator. Organizations of the future, however, are choosing a longer-term approach to producing results by investing in people. The most prized possession in these companies is the high level of accountability and collaboration among people. People are placed at the heart of the organization, and leaders recognize that their most important resource walks through the front door every day and will walk out again if they are uninspired. This book is for leaders and managers at all levels who believe that how people work together is the key to long-term success. Several premises underlie this belief: 1. People want to do their best. 2. People will give their discretionary effort when they are inspired. xi Copyright 2003 by The McGraw-Hill Companies, Inc. Click Here for Terms of Use. 3. People will produce unprecedented results with inspired leadership. Communication, language in particular, is the vehicle for unleashing the power of people. This is the tool that leaders use to either motivate people to reach higher or to derail them completely. Words are potent. They move the action forward or backward; there is no such thing as a neutral comment from a leader. All words have meaning and impact. Leaders who understand this can use language to harness the boundless energy of people toward focused business outcomes. Those who fail to recognize the power of their words will find themselves frustrated with the constant cycle of rework and communication breakdowns. The truth is that leadership competence, expertise, and commitment will not overcome poor communication skills. Most competent leaders and managers have been schooled, both formally and informally, in many different facets of leadership. But few have had the opportunity to learn how words shape reality and determine both their future and the future of the organization. This book closes the gap by providing leaders with much more than just tools; it explains why the tools work so leaders can easily apply powerful communication principles to the many challenges they face. Because words are potent, this book does not waste them. It is to the point, practical, and direct. No time is wasted on theory, academic research, or ego massage. This book is specifically designed for leaders and managers who are already successful and who want to achieve much more through their best resource people.